A comparative study of two various empirical methodologies for deriving kinetics of methane/steam reforming reaction. Issue 3 (September 2016) - Sciazko, A; Komatsu, Y; Washio, N; Brus, G; Kimijima, S; Szmyd, JS
Abstract: Despite methane/steam reforming is the conventional method for hydrogen production, there are widespread disagreements between formulations of the process kinetic derived in the literature. In the present research, the mathematical baseline of the classical calculation methodologies of the reaction kinetic are presented and compared. They include methodologies based on: I) the assumed constant partial pressure of steam and methane and II) the minimization of the summed relative standard deviation of the calculated reaction constant. Their results are compared with generalized least squares approach. The calculation methodologies are correlated with the planed experimental measurement set. This paper aims for the clarification of the observed differences and pointing the most suitable methodology for the decreasing the overall uncertainty of the model.